You've got a place here, too : an anthology of Black love stories set at HBCUs - LaDelle, Ebony; Harris, Kai; Ryan, Kennedy; Foley, Aaron; Acevedo, Elizabeth; Rochon, Farrah; Bruce, Carla; Yoon, Nicola; Bell, Jasmine; Platt, Christine A., 1976-; Laymon, Kiese; Walton, Dawnie (Delacorte Press, an imprint of Random House, 2025)
"A heartwarming and unforgettable collection of love stories set at Historically Black Colleges and Universities, exploring hope, endurance, and what it means to leave a legacy, from some of today's most prominent Black writers and edited by the acclaimed author of Love Radio"-- Provided by publisher.